Providing social guarantees as a component of corporate responsibility of construction enterprises - Zgalat-Lozynska , L. (Ways to Improve Construction Efficiency, 2023)
The article examines the importance of corporate social responsibility for construction companies as an important factor of their competitiveness and stability. The article considers social guarantees as a tool for increasing employee motivation, staff retention and ensuring safe working conditions, timely payment of wages, medical and insurance protection, as well as opportunities for professional development. The article analyses the implementation of social guarantees in the construction sector of Ukraine and their compliance with international standards, in particular, European ones. The key differences and prospects for improving social practices in domestic construction are identified. The economic and social effect of corporate social responsibility, its impact on labour productivity, company image and stakeholder trust are assessed. Particular attention is paid to the barriers to the implementation of corporate social responsibility, including financial constraints, instability of state regulation and insufficient level of corporate culture of responsible business. The author examines how these factors affect the implementation of social initiatives and suggests ways to overcome them. The article offers practical recommendations for integrating the principles of sustainable development into corporate strategy, adapting international standards of corporate social responsibility and creating transparent mechanisms for monitoring social obligations. It is recommended to involve employees more actively in decision-making processes, develop corporate culture and support initiatives that will help improve the efficiency of companies and the sustainable development of construction companies. In the future, transparent reporting and government support through tax incentives and grants will help to implement international standards of corporate social responsibility and improve the effectiveness of social guarantees in the construction industry.